2021
DOI: 10.1016/j.actbio.2021.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Tendinopathy and tendon material response to load: What we can learn from small animal studies

Abstract: Tendinopathy is a debilitating disease that causes as much as 30% of all musculoskeletal consultations. Existing treatments for tendinopathy have variable efficacy, possibly due to incomplete characterization of the underlying pathophysiology. Mechanical load can have both beneficial and detrimental effects on tendon, as the overall tendon response depends on the degree, frequency, timing, and magnitude of the load. The clinical continuum model of tendinopathy offers insight into the late stages of tendinopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 198 publications
(335 reference statements)
1
12
0
Order By: Relevance
“…The cause of elevated inflammation in repaired tendons may be due to multiple reasons including damage associated with suturing and loading of the tissue interface that may affect both tendon and muscle. 14 The effect of surgical repair on neighboring muscle is often understudied. In this study, we found that surgical repair promoted elevated MMP activity in muscle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cause of elevated inflammation in repaired tendons may be due to multiple reasons including damage associated with suturing and loading of the tissue interface that may affect both tendon and muscle. 14 The effect of surgical repair on neighboring muscle is often understudied. In this study, we found that surgical repair promoted elevated MMP activity in muscle.…”
Section: Discussionmentioning
confidence: 99%
“…This may limit the effect of physical therapy and exercise on Achilles tendons, which are known to adapt to mechanical loading. 13,14 Additionally, suturing may also stimulate inflammation in tendon similar to dry needling, 15 which may reduce its capacity to heal. Uncovering the biological and structural processes that differ between repaired (surgical repair) and non-repaired (nonsurgical repair) treatments may provide key insights into novel therapeutics to enhance Achilles tendon healing.…”
Section: Differences In Operative and Conservative Management Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…T he pathogenesis of tendinopathy is multifactorial and complex, and current treatment strategies are associated with variable efficacy and a high rate of recurrent symptoms, possibly owing to the poor regenerative potential of tendon and incomplete characterization of the underlying pathophysiology 1,33 . Our recent studies have revealed the role of mitochondrial dysfunction in the onset and progression of tendinopathy 3,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, multiscale investigations of tendon damage are critical to understanding how damage propagates spatially and temporally. In vivo animal models of tendon overuse and overload (such as treadmill running, repetitive reaching, climbing, direct tendon loading, and synergist ablation) have been used in such work ( Williamson et al, 2021 ; Bloom et al, 2023 ). Recently developed ex vivo model systems-designed to mimic in vivo tendon biomechanics and load the tendon in isolation-demonstrated that cyclically loading tendons to physiological stresses and strains results in temporal inflammatory as well as matrix degradation responses ( Benage et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%